Sesame Street let's cook together : with 40 fun, healthy recipes. (DK Publishing, 2024)
Elmo, Cookie Monster, and their friends from Sesame Street help make cooking fun by introducing 40 healthy and yummy recipes! Little chefs and their families will learn about healthy habits, food prep, cooking tools, and kitchen safety. With easy-to-follow instructions, clear photos, nutrition tips, and a guide for grown-ups, little Sesame Street-loving chefs will be inspired to prepare and eat healthy dishes that make them say, "Om nom, nom, nom!"